2022
DOI: 10.1186/s12889-022-14536-4
|View full text |Cite
|
Sign up to set email alerts
|

Mid-upper arm circumference as a substitute for body mass index in the assessment of nutritional status among adults in eastern Sudan

Abstract: Background Body mass index (BMI) remains the most used indicator of nutritional status despite the presence of a potentially credible alternative. Mid-upper arm circumference (MUAC) is an anthropometric measure that requires simple equipment and minimal training. The aim of this study was to compare MUAC with BMI and propose a MUAC cut-off point corresponding to a BMI of < 18.5 kg/m2 (underweight) and ≥ 30.0 kg/m2 (obesity) among Sudanese adults. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…Musa et al. [ 37 ] conducted a study in Sudan and reported that 51.1% of arm circumferences in both genders were malnourished using a MUAC cutoff of 25.5 cm for both genders with a BMI of less than 18.5 kg/m 2 [ 37 ]. Further studies conducted with children concluded that edema might increase a limb’s circumference, but it is not usually a problem of the upper arm [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Musa et al. [ 37 ] conducted a study in Sudan and reported that 51.1% of arm circumferences in both genders were malnourished using a MUAC cutoff of 25.5 cm for both genders with a BMI of less than 18.5 kg/m 2 [ 37 ]. Further studies conducted with children concluded that edema might increase a limb’s circumference, but it is not usually a problem of the upper arm [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…MUAC stands out as a cost-effective, quick, non-invasive, and easily measurable anthropometric index [ 60 ], and it can be employed in research studies to identify individuals with central obesity and insulin resistance in type 2 diabetes [ 61 ]. In comparison to the BMI method, MUAC presents clear benefits, particularly in its straightforward measurement without requiring mathematical derivation [ 62 ]. In an observational multinational cross-sectional study including 9–11-year-old children from 12 countries, MUAC was demonstrated as an alternative screening measure for obesity [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were instructed to expose the non-dominant side of their body and relax their arm. The circumference of the midpoint between the acromion and olecranon of the arm 30 was measured in centimeters (cm) with a precision of 0.1, and the average of the two measurements was used as the final result in this study.…”
Section: Methodsmentioning
confidence: 99%